2017
DOI: 10.12681/mms.1682
|View full text |Cite
|
Sign up to set email alerts
|

Growth and reproduction of the squid Illex coindetii Verany, 1839 in the central Mediterranean Sea

Abstract: Life span, growth and cost of reproduction of Illex coindetii were examined for the first time in the southern Adriatic Sea, central Mediterranean Sea. Age and growth were investigated through statoliths reading. Cost of reproduction was explored by studying the relative investment between somatic and gonad growth. The life span of I. coindetii was less than nine months in both sexes. Females (128-234 days) showed longer life span than males (124-178 days). In both sexes the linear model best described the man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The growth and lifespan of Illex coindetii were examined for the first time from fishing in deep water off the Egyptian Mediterranean Sea noted two age groups with zero group of male and three age groups with zero group of females and sexes combined. This is comparable to (González et al, 1996;Sánchez et al, 1998;Arkhipkin et al, 2000Ceriola et al 2016) stated that the lifespan of females I. coindetii usually showed a faster growth rate and longer than males. Table ( 5) shows that lifespan estimates of I. coindetii vary from (6 to 24 months).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The growth and lifespan of Illex coindetii were examined for the first time from fishing in deep water off the Egyptian Mediterranean Sea noted two age groups with zero group of male and three age groups with zero group of females and sexes combined. This is comparable to (González et al, 1996;Sánchez et al, 1998;Arkhipkin et al, 2000Ceriola et al 2016) stated that the lifespan of females I. coindetii usually showed a faster growth rate and longer than males. Table ( 5) shows that lifespan estimates of I. coindetii vary from (6 to 24 months).…”
Section: Discussionsupporting
confidence: 83%
“…(Mangold-Wirz, 1963a) in the western Mediterranean Sea, used length frequency analysis and concluded that the life span 20 and 24 months for males and females respectively. (Ceriola and Milone 2016) recorded female lifespan ranged from128 to 234 days longer than males 124-178 days. The variances in lifespan are due to the differences of individual size in the sample and in environmental condition especially temperature which affected on growth.…”
Section: Discussionmentioning
confidence: 95%
“…As recorded elsewhere in its range, in the East Mediterranean (Adriatic and Aegean Seas), I. coindetii is an intermittent terminal spawner (Ceriola and Milone, 2017;Salman, 2017). Alongside the apparent expansion of the species into the Northern North Sea and Baltic Sea Oesterwind and Schaber, 2020), there is now evidence of a summer spawning stock of Illex coindetii in the North Sea.…”
Section: Life Historymentioning
confidence: 69%